Rekonstruksi Konseptual Peradilan sebagai Revitalisasi Kekuasaan Kehakiman dalam Sistem Ketatanegaraan Indonesia - Hanif Fudin Al-Azhar (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2019)
Indonesia as a legal state is the logical consequence of the crystallization of Indonesian history as a nation both historically and constitutionally. Hence, Indonesia should has accountable constitutional system in law enforcement as well as social prestige to increase public trust in the justice system in Indonesia. In this study, the researcher is more focus on the justice system as the law enforcement. This study aims to investigate the inclusion of imbalance authority in Indonesia judicial system; between the Constitutional Court authority and the Supreme Court in testing legislation. Thus, intended conceptual reconstruction is a form of actualization as well as recommendation on the justice system that must be integrated in the two judicial institutions authority. Therefore, this research is conducted methodically as literal-descriptive research by addressing relevant data literally.